Avaliação da pressão arterial, frequência cardíaca, albuminúria e filtração glomerular estimada em pacientes submetidas à estimulação ovariana para fertilização in vitro - Musachio, Roberta Soletti (2014)
OBJECTIVE: To evaluate blood pressure (BP), heart rate (HR), albuminuria (AL), and glomerular filtration rate (GFR) of patients undergoing ovarian stimulation to in vitro fertilization (IVF). METHODS: From March to September 2013 this quasi-experimental design analyzed the variation of baseline and after BP levels, HR, AL, and GFR from 75 subjects, before embryo transfer. Blood pressure was measured after a five minutes at rest. Glomerular filtration was estimated by CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equation. Follicular growth was assessed using serial ultrasound scans. RESULTS: Median patient age was 36,89 years. Thirty-three (44%) women got pregnant, and 9 (12%) cycles were complicated by ovarian hyperstimulation. No statistically significant associations were found between systolic BP levels (P=0,945), diastolic BP levels (P=0,802), and GFR (P=0,301) before and after ovarian stimulation. However, this study found a statistically significant correlation of HR (P=0,012) and AL (P=0,002) with ovarian stimulation. There was no statistically significant difference in the modification of variables before and after stimulation between patients who got pregnant from those who did not pregnant, as well as the group who developed ovarian hyperstimulation compared with group that developed the expected number of follicles. Three patients developed acute kidney injury. CONCLUSION: Ovarian stimulation to IVF does not change the BP levels, and GFR of patients undergoing it. There is statistically significant increasing of HR and AL, but without clinical relevance. Pregnancy and ovarian hyperstimulation does not alter the pattern of the study variables.